THE IMPORTANCE OF FOREIGN LANGUAGE TEACHING - Yusupova , Hilola Umarali qizi (Educational Research in Universal Sciences, 2024)
English teaching is not so an easy job for the educators. It requires concrete syllabus including teaching methods, set of games and visual aids. The article explains the types of approaches and methods; aims of teaching EFL, focusing lessons to four skills: reading, writing, listening and speaking.